1939
DOI: 10.1042/bj0331655
|View full text |Cite
|
Sign up to set email alerts
|

Vitamins in rat's and in guinea-pig's milk

Abstract: THE development of a technique for the satisfactory milking of small laboratory animals [Cox & Mueller, 1937; Temple & Kon, 1937] and the recent progress in the chemical and physical estimation of various vitamins have made it possible to measure several of these factors in the milk of rats and of guinea-pigs. We have examined the milks of both species for vitamin A and carotene, vitamin B1, riboflavin and vitamin C. We have also studied the effect of changes in the diet on the levels of these factors in rat's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1942
1942
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…In particular, the activity and gene expression of BCO1 is induced in rat small intestine during the suckling‐weaning transition period, between days 13 and 27 after birth , probably to prepare the animals for BC absorption and metabolism from solid food. Consistently, rat milk contains no measurable levels of carotenes . Thus, lack of the full complement in BCO1 intestinal activity could explain that pups were only able to metabolize a fraction of the absorbed BC.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the activity and gene expression of BCO1 is induced in rat small intestine during the suckling‐weaning transition period, between days 13 and 27 after birth , probably to prepare the animals for BC absorption and metabolism from solid food. Consistently, rat milk contains no measurable levels of carotenes . Thus, lack of the full complement in BCO1 intestinal activity could explain that pups were only able to metabolize a fraction of the absorbed BC.…”
Section: Discussionmentioning
confidence: 99%
“…Methods based on the fluorescence of lactoflavin and of thiochrome, a derivative of vitamin B x , in ultra-violet light have been applied to the determination of these vitamins in various products (76,77) and these methods, suitably modified, can be applied to milk probably with satisfactory accuracy (78,79,80,81,82,83). A test using the growth of the micro-organism Phycmnyces Blakesleanus has also been suggested for the estimation of vitamin B x and has been applied to milk(84) but the results yielded so far for milk in the reviewer's laboratory have not been very encouraging (85).…”
Section: Cow's Milk I Nutritional Value As Estimated In Laboratory Amentioning
confidence: 99%
“…thiamin, pyridoxine, and ascorbic acid have been shown to plateau in human breast milk at a maximum level after certain levels of intake have been reached (PRATT and HAMIL 1951;GOPALAN and BELAVADY 1961;VENTLJRA and RINDI 1965;WEST and KIRKSEY 1976). The possibility that a protective mechanism exists was also suggested in a study by HOUSTON and KON (1939) who found that massive doses of thiamin administered to rats did not raise the thiamin level of their milk. In the present study dietary thiamin, ranging from 0.5-36 mg/kg did not cause thiamin saturation in milk.…”
Section: Discussionmentioning
confidence: 95%